The Mother's House - Verster, François (South Africa : Luna Films, 2006)
Three generations of the Moses family - Miche, her mother Valencia and Valencia's mother Amy - live together in a small house in Cape Town's Bonteheuwel community, an Apartheid-produced ghetto pierced by domestic violence and gangsterism. A richly detailed and deeply emotional portrait of the Moses women is created with their alternate affection and animosity toward one another, their reactions to the pervasive violence surrounding them, and their endeavors to find their own unique places and selves within that community and their tight-knit family unit. The film shows the women at home and in the streets around their home, and men are almost entirely absent in both places-only boys of Miche's age appear at all. Each woman's story is indicative of her time of life: teenage Miche's coming-of-age, her mother's pregnancy and her grandmother's reflections on errors of the past.
Keywords: Documentary films